2021
DOI: 10.3390/biology10060466
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Structural Mechanism for Sister Chromatid Cohesion Establishment at the Eukaryotic Replication Fork

Abstract: Cohesion between replicated chromosomes is essential for chromatin dynamics and equal segregation of duplicated genetic material. In the G1 phase, the ring-shaped cohesin complex is loaded onto duplex DNA, enriching at replication start sites, or “origins”. During the same phase of the cell cycle, and also at the origin sites, two MCM helicases are loaded as symmetric double hexamers around duplex DNA. During the S phase, and through the action of replication factors, cohesin switches from encircling one paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 117 publications
(184 reference statements)
0
2
0
Order By: Relevance
“…Various models have been suggested for the mechanism by which the two sister chromatids are held together (reviewed by [190]). In principle, a cohesin complex could form a large ring, which could embrace the two sister chromatids within the central cavity.…”
Section: Sister Chromatid Cohesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various models have been suggested for the mechanism by which the two sister chromatids are held together (reviewed by [190]). In principle, a cohesin complex could form a large ring, which could embrace the two sister chromatids within the central cavity.…”
Section: Sister Chromatid Cohesionmentioning
confidence: 99%
“…Indeed, many biochemical studies have confirmed that cohesin can form clusters or dimers in vivo [195,196]. The exact mechanism of action is still debated (reviewed by [190]). Cohesin holds the sister chromatids together until anaphase, when the Mcd1 subunit is cleaved by the Esp1 separase [197,198].…”
Section: Sister Chromatid Cohesionmentioning
confidence: 99%